2017
DOI: 10.1080/09540105.2017.1350637
|View full text |Cite
|
Sign up to set email alerts
|

Humoral immune response in mice immunized by oral route with phaseolamine extracted from common bean (Phaseolus vulgaris)

Abstract: The prevalence of obesity is increasing in Brazil, generating high costs for the health system. In the search for alternative therapies to control the obesity, several researches seek active compounds in natural products in order to find better pharmacological effects. Inhibitors of α-amylase such as phaseolamine extracted from common beans (Phaseolus vulgaris) have shown satisfactory results in weight loss. The present study aimed to verify the possibility of phaseolamine-causing allergic reactions through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Furthermore, the authors did not detect IgG1 and IgE in serum, diverging with the results found in the present study, suggesting that soy consumption should be cautious, due to its allergenic potential. Similarly, Silva et al (2017) also identified the presence of IgG and did not detect IgG1 and IgE in the investigation of the humoral immune response in mice sensitized with phaseolamine.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the authors did not detect IgG1 and IgE in serum, diverging with the results found in the present study, suggesting that soy consumption should be cautious, due to its allergenic potential. Similarly, Silva et al (2017) also identified the presence of IgG and did not detect IgG1 and IgE in the investigation of the humoral immune response in mice sensitized with phaseolamine.…”
Section: Discussionmentioning
confidence: 99%